Pneumonitis in Adult Onset Still’s Disease: Uncommon or Under Diagnosed? - Fernandes, Silvia (2017)
The adult onset Still’s Disease is an uncommon entity characterized by multiple clinical manifestations. Pneumonitis, less often considered, deserves particular emphasis given the need for differential diagnosis and because it can progress to severe respiratory failure. With the aim to highlight the pulmonary parenchyma involvement in patients with adult onset Still’s Disease, we present a case report which progresses with pneumonitis.